Do Sensory Stimulation Programs Have an Impact on Consciousness Recovery? - Cheng, Lijuan; Cortese, Daniela; Monti, Martin M.; Wang, Fuyan; Riganello, Francesco; Arcuri, Francesco; Di, Haibo; Schnakers, Caroline (Frontiers in Neurology, 2018)
Objectives. Considering sensory stimulation programs (SSP) as a treatment for disorders of consciousness is still debated today. Previous studies investigating its efficacy were affected by various biases among which small sample size and spontaneous recovery. In this study, treatment-related changes were assessed using time-series design in patients with disorders of consciousness (i.e., vegetative state – VS and minimally conscious state – MCS). Methods. A withdrawal design (ABAB) was used. During B phases, patients underwent a SSP (3 days a week, including emotional auditory, visual, tactile, olfactory and gustatory stimulation). The program was not applied during A phases. To assess behavioral changes, the Coma Recovery Scale-Revised (CRS-R) was administered by an independent rater on a weekly basis, across all phases. Each phase lasted 4 weeks. In a subset of patients, resting state functional magnetic resonance imaging (fMRI) data were collected at the end of each phase. Results. Twenty nine patients (48±19 years old; 15 traumatic; 21 > a year post-injury; 11 VS and 18 MCS) were included in our study. Higher CRS-R total scores as well as higher arousal and oromotor susbcores were observed in the B phases (treatment) as compared to A phases (no treatment), in the MCS group but not in the VS group. In the 3 patients who underwent fMRI analyses, a modulation of metabolic activity related to treatment was observed in middle frontal gyrus, superior temporal gyrus as well as ventro-anterior thalamic nucleus. Conclusion. Our results show higher CRS-R total scores when treatment is applied, and more exactly, increased arousal and oromotor function, which seems in line with our preliminary neuroimaging findings. Finally, our results suggest that, even if it may not be sufficient to restore consciousness, SSP might lead to improved behavioral responsiveness in MCS patients when using emotional stimulation.